2014 IEEE Antennas and Propagation Society International Symposium (APSURSI) 2014
DOI: 10.1109/aps.2014.6905075
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a cavity-backed capacitively-fed folded slot antenna using DOE techniques

Abstract: In this work a cavity-backed, capacitively-fed foldedslot antenna was characterized using Design of Experiments (DOE) techniques to study the influence of the antenna dimensions in the resonant frequency and in the reflection coefficient at resonance. The DOE technique used in the experiment was an un-replicated full factorial. The experiment was conducted by simulations in the Ansoft's HFSS, and the results obtained were statistically analyzed with the software Minitab. The results reflect with a 99% of relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The concept of Design of Experiments (DOE), particularly its Response Surface Methodology (RSM), is well suited for such a study even though the use of this technique was reported very little in the literature of electromagnetic research. A cavity backed, folded-slot antenna was characterized using DOE technique to study the effects of antenna dimensions on resonant frequency and reflection coefficient at resonance [8]. A full factorial design with no replication was employed here to obtain regression equations for the aforesaid response variables.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Design of Experiments (DOE), particularly its Response Surface Methodology (RSM), is well suited for such a study even though the use of this technique was reported very little in the literature of electromagnetic research. A cavity backed, folded-slot antenna was characterized using DOE technique to study the effects of antenna dimensions on resonant frequency and reflection coefficient at resonance [8]. A full factorial design with no replication was employed here to obtain regression equations for the aforesaid response variables.…”
Section: Introductionmentioning
confidence: 99%